Identity and Agency in England, 1500–1800
XI, 254 p. 2 illus.
Keywords: This collection of essays is arranged around the central issue raised by a raft of new empirical research - the relationship between social identity, or the 'vision of the self', and the ways in which this can explain historical agency. If identities in early modern society were multiple, complex, and dependent on context, rather than homogenous, consistent, or easily determined, then it is difficult to make simple causal links to behaviour. This collection aims to make innovative new research on the structures of English society available to the wider scholarly audience. The essays use a number of detailed contextual case studies to explore the twin themes of the nature of identities in early modern society, and their role in influencing historical agency. They examine the variety of identities available to individuals in early modern England, and the ways in which these were invoked and employed.